Answer:
42. Graph a
43. Not possible.
44. Graph e
45. Graph c
46. Graph b.
Step-by-step explanation:
42. 7x + 13 ≥ 55
⇒ x ≥ 6
So, it matches graph a.
43. 12x - 8 > 4(3x + 2)
⇒ 12x - 8 > 12x + 8
Hence, d. not possible.
44.
⇒
⇒ x > - 8
Hence, graph e matches.
45. - 4(- 2x + 3) ≤ 5 + 8x
⇒ 8x - 12 ≤ 5 + 8x
⇒ - 12 ≤ 5
This is true for all values of x, hence that matches graph c.
46. - 4(x + 3) > 8(x + 3)
⇒ - 4x - 12 > 8x + 24
⇒ 12x < - 36
⇒ x < - 3
Hence, graph b matches the situation. (Answer)
If an angle is 70 degrees and there is an angle vertical to it, then that other angle also equals 70 degrees. Therefore, if angle X equals 40 degrees, then angle Y also equals 40 degrees. Hope this helps.
Angles are classified based on their measures.
<u>Classification of angles</u>
The following are the classification of angles
- Acute Angles
- Right Angles
- Obtuse Angles
- Straight lines
- Reflex Angles
The smallest angle is 0 degrees and the largest is 360 degrees.
When the measure of an angle is less than 90 degrees, such angle is an acute angle
When the measure of an angle is exactly 90 degrees, such angle is a right angle
Angles greater than 90 degrees, but less than 180 degree are obtuse angles, while angles that measure exactly 180 degrees are straight lines.
The last type of angle is the reflex angle, and it has a measure between 180 degrees and 360 degrees (exclusive)
<em>The question is incomplete, so I gave a general explanation</em>
Read more about angles at:
brainly.com/question/17972372
Answer:
1. (a-c)
+ b![\sqrt{y}](https://tex.z-dn.net/?f=%5Csqrt%7By%7D)
2. 9m + 2![\sqrt{n}](https://tex.z-dn.net/?f=%5Csqrt%7Bn%7D)
3. 6a
4. (5a - 3b)![\sqrt{5y}](https://tex.z-dn.net/?f=%5Csqrt%7B5y%7D)
Step-by-step explanation:
1. since a and c share the same squareroot x, you can combine these together.
2. First add like terms together. 4m - m + 6m = 9m. Then 5
and -3
combined equals 2![\sqrt{n}](https://tex.z-dn.net/?f=%5Csqrt%7Bn%7D)
3. First simplify the square roots. squareroot of 16 is 4. square root of 49 is 7. square root of 81 is 9. They are all multiplied by a in the expression. Thus 4a - 7a + 9a = 6a
4. First simplify the radicals, they are not perfect. square root of 125 is equivalent to sqrt(25 * 5), which sqrt of 25 is 5, but we keep the sqrt of 5. For sqrt of 45, it is the same as sqrt9 * sqrt5. sqrt of 9 is the same as 3 and we keep sqrt 5. Thus we get the below:
5a
- 3b![\sqrt{5y}](https://tex.z-dn.net/?f=%5Csqrt%7B5y%7D)
We can combine the two like terms and get the final answer above.
please give thanks by clicking the heart :)
Answer:
28
Step-by-step explanation:
i think hope this helps